FENOMENA CANCEL CULTURE, KECAMAN KOMUNIKASI, DAN KESEHATAN MENTAL NETIZEN DI INSTAGRAM - Latief, Rahmawati (Jurusan Bimbingan dan Penyuluhan Islam, 2023)
Cancel culture is a phenomenon that arises because of the implications of a combination of popular culture, and cyberpsychology. The purpose of this study was to find out the public's interpretation of the cancel culture phenomenon experienced by Taufik Hidayat, an Indonesian badminton legend associated with criticism of verbal communication on Instagram as well as reviews from a mental health perspective. This research uses the corpus of April 23, 2023 posts on the Instagram account @Taufikhidayatofficial which reached 48,716 comments and 27,307 likes. The research uses qualitative methods by adopting Teun A.van Dijk's discourse analysis techniques, namely macrostructure, superstructure, and micro structure. The results of the study show that the public's interpretation expresses verbal criticism of racism between the two countries, personal legends of badminton between the two countries, and criticism of the Malay language which is supported by assertive language styles, satire up to the frontal. From a mental health perspective, the cancel culture phenomenon can have psychological impacts such as the emergence of shame, being vulnerable to cyberbullying, being exposed to isolation and loneliness, requiring perfectionists to appear, experiencing depression, experiencing fear of interacting in cyberspace and the real world, experiencing social sanctions from society, the emergence online bullies, requiring two-faced appearances because they generally use anonymous accounts by disguising their real identities, appearing as dusty (origin) aliases without data and facts, appearing as satirists, to people with nomophobia (no-mobile-phone) and people with illnesses fomo (fear of missing out).